Role of protein S in castration-resistant prostate cancer-like cells. Issue 8 (August 2016) - Ning, Peng; Zhong, Jia-guo; Jiang, Fan; Zhang, Yi; Zhao, Jie; Tian, Feng; Li, Wei
Abstract : Understanding how castration-resistant prostate cancer (CRPC) cells survive the androgen-deprivation condition is crucial for treatment of this advanced prostate cancer (PCa). Here, we reported for the first time the up-regulation of protein S (PROS), an anticoagulant plasma glycoprotein with multiple biological functions, in androgen-insensitive PCa cells and in experimentally induced castration-resistant PCa cells. Overexpression of exogenous PROS in LNCaP cells reduced androgen deprivation-induced apoptosis and enhanced anchorage-dependent clonogenic ability under androgen deprivation condition. Reciprocally, PROS1 knockdown inhibited cell invasiveness and migration, caused the growth inhibition of castration-resistant tumor xenograft under androgen-depleted conditions, and potentiated Taxol (a widely prescribed anti-neoplastic agent)-mediated cell death in PC3 cells. Furthermore, PROS overexpression significantly stimulated AKT activation but failed to evoke oxidative stress in LNCaP cells under normal condition, suggesting that the malignance-promoting effects of the above-mentioned pathway may occur in the order of oxidative stress/PROS/AKT. The potential mechanism may be due to control of oxidative stress-elicited activation of PI3K-AKT-mTOR pathway. Taken together, our gain-of-function, loss-of-function analyses suggest that PROS may facilitate cell proliferation and promote castration resistance in human castration-resistant PCa-like cells via its apoptosis-regulating property. Future study emphasizing on delineating how PROS regulate cellular processes controlling transformation during the development of castration resistance should open new doors for the development of novel therapeutic targets for CRPC.